A modeling exercise to show why population models should incorporate distinct life histories of dispersers. Issue 2 (17th December 2020) - Deere, Jacques A.; van den Berg, Ilona; Roth, Gregory; Smallegange, Isabel M.
Abstract: Dispersal is an important form of movement influencing population dynamics, species distribution and gene flow between populations. In population models, dispersal is often included in a simplified manner by removing a random proportion of the population. Many ecologists now argue that models should be formulated at the level of individuals instead of the population level. To fully understand the effects of dispersal on natural systems, it is therefore necessary to incorporate individual‐level differences in dispersal behavior in population models. Here, we parameterized an integral projection model, which allows for studying how individual life histories determine population‐level processes, using bulb mites, Rhizoglyphus robini, to assess to what extent dispersal expression (frequency of individuals in the dispersal stage) and dispersal probability affect the proportion of successful dispersers and natal population growth rate. We find that allowing for life‐history differences between resident phenotypes and disperser phenotypes shows that multiple combinations of dispersal probability and dispersal expression can produce the same proportion of leaving individuals. Additionally, a given proportion of successful dispersing individuals result in different natal population growth rates. The results highlight that dispersal life histories, and the frequency with which disperser phenotypes occur in the natal population, significantly affect population‐level processes. Thus, biological realism of dispersal population models can be increased by incorporating the typically observed life‐history differences between resident phenotypes and disperser phenotypes, and we here present a methodology to do so. Abstract : We used an integral projection model that incorporated distinct life histories of disperser‐ and resident phenotypes to determine the role of disperser phenotypes on natal population processes. With this model, we investigated to what extent the frequency of individuals developing into disperser phenotypes (probability of dispersers) and the probability that disperser phenotypes emigrate (dispersal probability) affect population growth rate and the proportion of successful dispersing individuals. We find that when allowing for life‐history differences between disperser and resident phenotypes, multiple combinations of probability of dispersers and dispersal probabilities can produce not only the same proportion of leaving individuals but also the same population growth rate.